Enhancement of the Hydrodynamic Characteristics in Shell-and-Tube Heat Exchangers by Using W-Baffle Vortex Generators - Menni, Younes; Chamkha, Ali J.; Ameur, Houari; İnç, Mustafa (Budapest Univ Technology Economics, 2020)
Improving the hydrodynamic characteristics of STHECs (Shell-and-Tube Heat Exchanger Channels) by using BVG5 (Baffle-type Vortex Generators) is among the common passive methods due to their proved efficiency. In this computational investigation, the same method is used to enhance the hydrodynamic behavior of STHEC5, by inserting W-shaped Baffle-type Vortex Generators. The numerical model represented by the computational FVM (Finite Volume Method) is used to simulate and analyzed the considered physical model. The fluid used is air, its thermal physical properties are constant, turbulent, incompressible, and its temperature is 300 K at the inlet section of the STHEC. The flow velocity (U-in) and atmospheric pressure (P-atm) are considered as boundary conditions at the entrance (x = 0) and exit (x = L) of the channel, respectively. The results showed that the friction coefficients were related to the pressure, velocity, and Reynolds number values. High values of Re yielded an acceleration of the fluid, resulting thus in increased pressure on the solid walls and augmented friction values.
Keywords: hydrodynamic aspect; W-shaped baffle; rectangular channel; turbulent flow; air-fluid; numerical simulation